A Feasibility Study of Low-Power Laser Trepanning Drilling of Composite Using Modified DVD Writer - Nurfairuz Nadirah, Binti Affandi; Khairul Fikri, Bin Tamrin; Amir Azam, Khan; Moghadasi, Kaveh; Mohd Ridzuan, Bin Mohamad Sharip; Shahrol, Mohamaddan; Anamul, Hossain (Universiti Tun Hussein Onn, 2020)
In the present study, laser cutting of cotton fiber composite laminate is experimented using a modified DVD writer drive. A 250 mW diode laser is initially extracted from a DVD writer drive, and then regulated by a custom-made laser driver circuit designed using a Proteus® software. Experimental tests are carried out using multi -pass laser trepanning drilling at different drilling speeds and standoff distances (SODs). The cut quality is evaluated by measuring the extent of both oxide and resolidified resin regions. It was discovered high speed of trepanning drilling and positive SOD significantly improve cutting region quality. Furthermore, positive and negative SODs require relatively high number of passes at different drilling speeds. From SEM micrographs, it is found out that the crack formation and fiber protruding happen in thedrilling area due to thermal stresses and matrix vaporization